THE TRAGEDY OF FERGHANA AND ITS NEGATIVE ASPECTS - Khabibullo Khakimovich Khusanov (Journals Park Publishing, 2023)
The article analyzes the tragedy of Ferghana that took place in the Ferghana region in the last years of Soviet power, the causes of these inter-ethnic problems with the help of primary sources, periodicals and scientific literature.
Keywords: Ferghana region, Ferghana tragedy, Meskhetian Turks, interethnic conflict, colonialism, food problem.